2018
DOI: 10.1186/s12909-018-1429-2
|View full text |Cite
|
Sign up to set email alerts
|

An overview of osteopathy graduates’ perceived preparedness at transition from educational environment to clinic environment one year after graduation: a cross sectional study

Abstract: BackgroundThis study investigated perceived preparedness to practice, one year after graduation across osteopathic education institutions (OEIs) and explored possible differences between countries where osteopathy is regulated (Reg) and countries where it is not (Unreg).MethodsTwo hundred forty-five graduates from 7 OEIs in 4 European countries, already assessed in a previous study, were contacted one year after their graduation to complete the survey. Survey tools included a questionnaire to assess perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Osteopathy is a complementary touch-based manual medicine primarily used by different age groups of patients ( Licciardone et al, 2013 ; Cerritelli et al, 2014 , 2015b ; Pizzolorusso et al, 2014 ; Luciani et al, 2015 , 2018 ; Schwerla et al, 2015 ; Steel et al, 2017 ) and in a wide variety of clinical conditions ( Cerritelli et al, 2011 , 2015a , 2016a , 2017b ; Cicchitti et al, 2015 ; Ruffini et al, 2016 ; Franke et al, 2017 ; Lanaro et al, 2017 ). Several studies showed positive clinical effects as compared to sham, placebo, usual care or physical devices ( Pizzolorusso et al, 2011 ; Cerritelli et al, 2013 , 2015a , 2016b ; Martelli et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osteopathy is a complementary touch-based manual medicine primarily used by different age groups of patients ( Licciardone et al, 2013 ; Cerritelli et al, 2014 , 2015b ; Pizzolorusso et al, 2014 ; Luciani et al, 2015 , 2018 ; Schwerla et al, 2015 ; Steel et al, 2017 ) and in a wide variety of clinical conditions ( Cerritelli et al, 2011 , 2015a , 2016a , 2017b ; Cicchitti et al, 2015 ; Ruffini et al, 2016 ; Franke et al, 2017 ; Lanaro et al, 2017 ). Several studies showed positive clinical effects as compared to sham, placebo, usual care or physical devices ( Pizzolorusso et al, 2011 ; Cerritelli et al, 2013 , 2015a , 2016b ; Martelli et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The osteopathic profession in Italy has undergone progressive feminisation since its inception [ 12 ]. This data seems to be more evident in a European study [ 16 ] in which the study sample was predominantly composed of female students (73.8%). Despite the fact that the authors declared that the selected sample might have not been representative of the population of European osteopathy students, it might be speculated that, if the same trend applied to other countries in which the osteopathic profession has been established prior to than in Italy (e.g., the UK), the observed ratio might be plausible.…”
Section: Discussionmentioning
confidence: 77%
“…In recent years, a great effort has been made, in the scientific production, to profile the osteopathic professionals in many countries [ 11 16 ]. One study that aimed to profile osteopathic practitioners in countries without statutory regulations in osteopathy was the Benelux study [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the World Health Organization (WHO) osteopathy relies on manual contact for diagnosis and treatment, replacing the definition initially proposed by the World Osteopathic Health Organization. There exists a large heterogeneity in recognition and regulation of the practice of osteopathy across different countries, sometimes depending on whether practitioners are admitted to the medical community or not 2,3 . This increasing interest in osteopathic medicine may reflect the reality of the society as patients turn to complementary or alternative treatments when conventional treatments seem to fail in producing the desired outcome, or produce side effects 4,5 .…”
Section: Introductionmentioning
confidence: 99%